2022
DOI: 10.1101/2022.01.10.22268859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation in US Drug Overdose Mortality Within and Between Hispanic/Latine Subgroups: A Disaggregation of National Data

Abstract: This study examined differences across Latine heritage groups (i.e., Mexican, Puerto Rican, Cuban, Dominican, Central American, South American) in rates of US drug overdose mortality. The study utilized 2015-2019 mortality data from the National Center for Health Statistics for 29,137 Hispanic individuals who died of drug overdose. Using population estimates from the American Community Survey, age-standardized drug overdose mortality rates were calculated by specific Latine heritage and sex, nativity, educati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Although there may be some value gained when all H/L individuals are aggregated into a single group, the practice of categorizing H/L as a homogeneous ethnic group can hinder our understanding of patterns of drug use, with subsequent constraints on research to identify practical prevention and treatment strategies. Examples of research utilizing an ethnicity disaggregation approach have encompassed a variety of health outcomes, including, but not limited to, psychiatric morbidity ( Alegria et al., 2007 ; Alegria, et al., 2008 ), cigarette smoking ( Barnes, et al., 2010 ; Rodriguez et al., 2019 ); alcohol misuse ( Barnes, et al., 2010 ; Caetano et al., 2008 ; Lipsky & Caetano, 2009; Ramisetty-Mikler, et al., 2010 ; Rios-Bedoya & Freile-Salinas, 2014 ), drug misuse ( Lacey, et al., 2016 ; Parker et al., 2018 ), drug overdose (Cano, 2020; Cano & Gelpí-Acosta, 2022 ), and health care utilization ( Barnes, et al., 2010 ; Mancini, et al., 2015 ). Taken together, this research has demonstrated that data aggregation conceals within-group inequities in health-related issues in various populations including countries outside the U.S. ( Lacey, et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there may be some value gained when all H/L individuals are aggregated into a single group, the practice of categorizing H/L as a homogeneous ethnic group can hinder our understanding of patterns of drug use, with subsequent constraints on research to identify practical prevention and treatment strategies. Examples of research utilizing an ethnicity disaggregation approach have encompassed a variety of health outcomes, including, but not limited to, psychiatric morbidity ( Alegria et al., 2007 ; Alegria, et al., 2008 ), cigarette smoking ( Barnes, et al., 2010 ; Rodriguez et al., 2019 ); alcohol misuse ( Barnes, et al., 2010 ; Caetano et al., 2008 ; Lipsky & Caetano, 2009; Ramisetty-Mikler, et al., 2010 ; Rios-Bedoya & Freile-Salinas, 2014 ), drug misuse ( Lacey, et al., 2016 ; Parker et al., 2018 ), drug overdose (Cano, 2020; Cano & Gelpí-Acosta, 2022 ), and health care utilization ( Barnes, et al., 2010 ; Mancini, et al., 2015 ). Taken together, this research has demonstrated that data aggregation conceals within-group inequities in health-related issues in various populations including countries outside the U.S. ( Lacey, et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%